Effect of Atorvastatin Treatment on Vascular Aterogenic Factors (Lipid Profiles and VCAM-1) in Patient Diabetes with Dyslipidemia - Asri Wido Mukti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
To analyze effectiveness of atorvastatin 20mg on lipid profiles and adhesion molecule VCAM-1 in patient with diabetes dyslipidemia. An observational prospective cohort study was conducted from November 2016 to March 2017. Patients who fulfilled the inclusion criteria were taken twice for their lipid profiles and VCAM-1 measurements (before initiation of study and after 6 weeks treatment of atorvastatin 20mg). There were 13 patients who met the inclusion criteria. The results of 13 patients showed that after 6 weeks of atorvastatin therapy, there was a 28% decrease in total cholesterol (t0=223.77±49.69, t1=160.92±24.69), 39% LDL decrease (t0=152.59±44.25, t1 =93±21.44), a decrease in TG 38.6% (t0=200.85±101.53, t1=123.30±62.77) and a statistically significant decrease in VCAM-1 7.47% (t0=729.59±208.06, t1=675.06±182.88). The results of the correlation test between total cholesterol and VCAM-1 (p=0.185, r=0.268), LDL and VCAM-1 (p=0.127, r=0.307), TG and VCAM-1 (p=0.198, r=0.261) showed no correlation. Based on the results of the study, it can be concluded that atorvastatin therapy can provide improvements in atherogenic factors such as decreased lipid profile and VCAM-1, and there was no correlation between lipid profile and VCAM-1 in type 2 DM patients with dyslipidemia.